A prospective study of management of subtrochanteric femur fracture using proximal femoral nail - Malik, Shwetabh; Malviya, Parimal; Vieira, Alfven; Jain, Deepak (International Journal of Research in Orthopaedics, 2020)
Background: Proximal femur fractures present considerable challenge in management. They are due to high velocity trauma, with or without soft tissue injury and usually with a metaphyseal and diaphyseal involvement. The surgeon has to face many challenges like identifying the entry, reduction the fracture, and difficulty due to a narrow medullary canal and comminution. The present study was conducted to assess the utility and effectiveness of Proximal Femoral Nail for subtrochanteric fractures of femur. Methods: In this study a total of 30 patients with Sub trochanteric femur fracture admitted to MGM medical college and hospital from June 2015 to July 2017 were selected for treatment with proximal femur nail. Results: 30 patients were included in this study with subtrochanteric fractures of femur treated with Proximal femoral nail. Maximum 21(70%) of patients were below 61 yrs of age. Mean age was 47.9 years. There was 21 male and 9 females in the study. There were 6 patients with local complications. Final result of our study, we had 26.7% excellent, 46.6% good, 20% fair and 6.7 % poor results according to Harris hip score. Conclusions: In our study, looking at the results we found that Proximal femoral Nail proves to be a good implant in management of subtrochanteric fractures of femur. However, it is a small study to conclude anything definitely.